PENINGKATAN KETERAMPILAN BERBICARA MENGGUNAKAN METODE BERMAIN PERAN PADA SISWA SEKOLAH DASAR - Nur Rayhan; Rizki Ananda; Muhammad Syahrul Rizal; Ory Syafari Jamel Sutiyan (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2023)
This study aims to determine the use of the role-playing method in improving the speaking skills of elementary school students. The research location is in class V of SDN 005 Empat Balai, Kampar Regency, Riau Province. This research strategy is Classroom Action Research (CAR) which is carried out in two cycles. Each cycle consists of two meetings and four stages, namely planning, implementation, observation, and reflection. The subjects of this research were 21st grade 5 students, 7 male students and 10 female students. Data collection techniques in the form of documentation, observation, and tests. Based on the results of data analysis, it can be seen that the mastery of students' speaking skills in the first cycle reached 61.90% or from 21 students there were 13 students who completed. The improvement of students' speaking skills in the second cycle reached 85.71% or from 21 students there were 18 students who completed. Based on these results, it can be concluded that speaking skills using the role-playing method can increase in fifth grade students at SDN 005 Empat Balai